Uniaxial compaction of sand using 4D X-ray tomography: The effect of mineralogy on grain-scale compaction mechanisms. (March 2021) - Cuesta Cano, Andrea; Van Stappen, Jeroen F.; Wolterbeek, Timotheus K.T.; Hangx, Suzanne J.T.
Highlights: X-ray micro-CT imaging allows the investigation of sand pack compaction. Sand pack deformation is mainly accommodated by inelastic processes. Clays within pores and grain contacts facilitates grain sliding and rearrangement. Abstract: The mechanical behaviour of sand aggregates is often studied as a proxy for poorly consolidated sands and highly porous sandstones. Only recently research aimed at understanding sand deformation has started to use techniques that allow for direct observation of the in-situ grain-scale processes. Using state-of-the-art, time-lapse micro X-ray computed tomography (micro-XCT) imaging, the influence of mineralogy on the compaction of sand aggregates has been investigated by performing uniaxial compaction experiments on four different mineral assemblies (quartz, K-feldspar, quartz + K-feldspar and quartz + K-feldspar + clay) at room temperature and dry conditions. For the experiments, a bespoke uniaxial compaction device (sample diameter 2 mm) was constructed and coupled with micro-XCT imaging. This enabled in-situ observation of the strain-accommodating processes during deformation. To verify that the microstructural evolution observed in the small-scale experiments is representative for larger aggregate behaviour, conventional, centimetre-sized, control experiments were performed. The observed inelastic deformation was mainly accommodated by processes such as intragranular cracking and intergranular sliding. At low axial stresses (10 MPa), grain fracturing mainly occurred in K-feldspar grains, if present, along cleavage planes. Only at higher axial stresses, fracturing of quartz grains, if present, was also observed. Presence of clays, in pores and grain contacts, delayed the onset of quartz grain breakage and enhanced porosity reduction as clay in grain contacts facilitated grain sliding and rearrangement.